THE RELATIONSHIP BETWEEN CENTRAL OBESITY AND SLEEP QUALITY WITH MENSTRUAL CYCLE AMONG ADOLESCENT GIRLS AT MUHAMMADIYAH 3 SENIOR HIGH SCHOOL TULANGAN SIDOARJO - Okta Wanda Savitri; Dini Setiarsih (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Menstrual cycle disorders are common reproductive health issues among adolescent girls and are often associated with hormonal imbalances. Central obesity, characterized by abdominal fat accumulation, can disrupt hormonal regulation, while poor sleep quality may decrease melatonin production, both of which can affect the menstrual cycle. This study aimed to examine the relationship between central obesity and sleep quality with the menstrual cycle. A cross-sectional design was used involving 82 female students selected through stratified random sampling from a population of 240 students at SMA Muhammadiyah 3 Tulangan Sidoarjo. Waist circumference was measured using the midline method, sleep quality was assessed through a questionnaire, and menstrual cycle data were collected for the last three months. Data were analyzed using Spearman’s rank tests. The results showed that 34.1% of respondents experienced central obesity, 35.4% had poor sleep quality, and 45.1% had oligomenorrhea. There was a significant relationship between central obesity and sleep quality with the menstrual cycle. It is recommended that adolescent girls adopt healthy lifestyles and regulate sleep patterns to maintain reproductive health and prevent menstrual disorders.